2019
DOI: 10.1021/acs.joc.9b02987
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2-Dihydroisoquinolines by a Modified Pomeranz–Fritsch Cyclization

Abstract: Isoquinolines (IQs) and their derivatives are present in many natural products and biologically active small molecules. Herein, we report a modified procedure for the classical Pomeranz-Fritsch protocol, which expands the scope of 1,2-dihydroisoquinoline (DHIQs) products. 1,2-DHIQs are an attractive branch point for the synthesis of IQs, but because of their innate reactivity, they have remained difficult to prepare. We demonstrate that the Fujioka/Kita conditions, combining trimethylsiyltriflate (TMSOTf) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Ji and Lumb have also reported the similar Pomeranz‐Fritsch cyclization towards the synthesis of 1,2‐dihydroisoquinolines under Fujioka/Kita conditions [327] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 81%
See 1 more Smart Citation
“…Ji and Lumb have also reported the similar Pomeranz‐Fritsch cyclization towards the synthesis of 1,2‐dihydroisoquinolines under Fujioka/Kita conditions [327] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 81%
“…[37e] Ji and Lumb have also reported the similar Pomeranz-Fritsch cyclization towards the synthesis of 1,2-dihydroisoquinolines under Fujioka/Kita conditions. [327] Zhao et al have reported 1,1'-disubstituted and spiro-tetrahydroisoquinoline alkaloid 567 synthesis by employing biomimetic phosphate buffer following Pictet-Spengler reaction sequence. The tetrahydroisoquinolines were obtained in high yields (Scheme 329).…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…The use of the endocyclic enamine functional group of the partially reduced N -heteroarene has been challenging because it is readily rearomatized . A typical solution for this issue is the use of a protecting group; however, additional protection/deprotection steps are often required to achieve this. Recently, our group reported the cyclic amidine syntheses via dearomative hydrosilylation of readily available N -heteroarenes 1 (Scheme b). , The first B­(C 6 F 5 ) 3 catalyzed dearomative monohydrosilylation step could provide the unique endocyclic N -silyl enamine 2 as an intermediate. Although the N–Si bond of 3 is unstable under ambient conditions, 3 is stable enough to use in situ . The transient silyl protecting group was easily cleaved during the workup process.…”
mentioning
confidence: 99%
“…A substituent at C8 precludes the most common syntheses based on Pictet–Spengler or Bischler–Napieralski cyclizations to form the C1–C8a bond. Therefore, we devised an alternative that capitalized on Ellman’s chiral sulfonamide technology to install the lone chiral center at C1 and our recently reported modification of the Pomeranz–Fritsch cyclization to install the isoquinoline ring by forming the C4–C4a bond.…”
mentioning
confidence: 99%
“…Ellman’s auxiliary was then removed to allow reductive alkylation with a glyoxal dimethyl acetal ( 11 ) before tosyl protection of the amine provided 7 with >99% ee and in 83% yield on a scale of 7–9 g . To effect the desired Pomeranz–Fritsch cyclization, we employed our recently reported conditions, consisting of 3 equiv of TMS-OTf and 4 equiv of 2,6-lutidine. We were pleased to find that the cyclization of 7 to 15 proceeded in 83% yield on a 14 g scale without erosion of the ee .…”
mentioning
confidence: 99%